Fruit and seed exploitation by small rodents of the Brazilian Atlantic forest - Vieira, E. M.; Pizo, M. A. [UNESP]; Izar, P. (My University, 2003)
In the Brazilian Atlantic forest (BAF) there are at least 57 rodent species and most of them are considered omnivorous. These species feed, more or less frequently, on fruits and seeds. Nevertheless the potential role of each species as frugivorous, seed predator or seed disperser is still unclear. In the present study we analyzed patterns of fruit and seed exploitation by eight small rodent species from an Atlantic Forest site. We offered to captive animals fruits of 30 plant species (23 genera, 15 families). After 48 h we recorded consumption patterns of pulp/aril and seed. Rodent species differed in their patterns of fruit and seed exploitation. The smallest species, Akodon serrensis, Oligoryzomys nigripes, and Wilfredomys pictipes (body size range : 26-45 g), and also the medium-sized Oecomys aff. concolor (84 g) fed mainly on pulp and also on small to medium-sized seeds (< 10 mm diameter). The medium-sized rodent, Oryzomys russatus (91 g) fed on pulp and also on seeds with diameter ≤ 15 mm. Thus larger seeds remain intact after being manipulated by such species. The medium-sized Delomys dorsalis (72 g) and the larger Trinomys iheringi (274 g) and Nectomys squamipes (253 g) form a third group, which consumed both fruit and seed of most species independent of their size. These later two species and also O. russatus are probably the main seed predators in the rodent community of the BAF.
Keywords: Brazilian Atlantic forest; Exploitation; Fruits; Rodents; Seeds; dispersal; feeding behavior; fruit; predation; rodent; seed; Brazil; South America; Akodon; Akodon serrensis; Animalia; Delomys; Delomys dorsalis; Nectomys; Nectomys squamipes; Oecomys; Oligoryzomys nigripes; Oryzomys; Oryzomys russatus; Rodentia; Trinomys; Trinomys iheringi; Vertebrata; Wilfredomys; Wilfredomys pictipes